Job Creation and Job Destruction Dynamics in the U.S. Truck Transportation Industry, 1995-2019 - Jason W. Miller; Jonathan Phares; Stephen V. Burks (Institute of Labor Economics (IZA), 2023)
Every year, approximately 27% of all jobs in the U.S. truck transportation sector (NAICS 484) are reshuffled across motor carriers as existing carriers grow or shrink, new entrants begin operations, and existing firms exit. Studying how these dynamics unfold, especially for young carriers, is critical to further our understanding of employment dynamics in the U.S. trucking industry. This manuscript takes a first look at job creation and job destruction dynamics in truck transportation, with a special emphasis on the roles of carrier age and on job creation and destruction dynamics in the manufacturing sector, the source of demand for most trucking ton-miles. In doing so, we draw on and extend theory in both supply chain management and economics. We test our predictions using archival data from the U.S. Census Bureau's Business Dynamics Statistics program that tracks the universe of truck transportation firms with employee establishments from 1995 through 2019, focusing on firms that are ten years old or younger. Results from fitting a series of linear mixed effects models provide strong evidence that job creation and job destruction dynamics at trucking firms decline rapidly as carriers age. We further find these age-related dynamics are moderated by employment dynamics in the manufacturing sector. We discuss implications of these findings for theory and practice.
Keywords: J21; J63; L92; 330; job creation; job destruction; motor carrier; U.S. trucking industry; business dynamics statistics